2022
DOI: 10.3390/children9071015
|View full text |Cite
|
Sign up to set email alerts
|

When Are Children Most Physically Active? An Analysis of Preschool Age Children’s Physical Activity Levels

Abstract: The levels of physical activity (PA) in the population have decreased, especially at an early age. The aims of the study were: to evaluate the percentage of children meeting PA recommendations for both genders, and to measure steps and PA level at different time intervals during the week. This was an observational cross-sectional study. Seventy-three schoolchildren (36 boys and 37 girls), aged two years (2.12 ± 0.46), were selected to participate in this study. Participants wore an “Actigraph GT3X” acceleromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(64 reference statements)
0
5
0
4
Order By: Relevance
“…En relación a las variables relacionadas con los dispositivos inteligentes para la medición de la AF, se aprecia el predominio de los acelerómetros, instrumento indudablemente más objetivo (Martínez-Vizcaino y Sánchez-López, 2008;Calahorro et al, 2015). De hecho, existen estudios que comienzan a valorar la AF con acelerometría desde los dos años de edad (Díaz-Quesada et al, 2022). Es cierto que, si se analiza la marca de estos dispositivos inteligentes, el abanico es muy amplio, no existiendo un predominio marcado ni concreto por uno de ellos (Wijndaele et al, 2015).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En relación a las variables relacionadas con los dispositivos inteligentes para la medición de la AF, se aprecia el predominio de los acelerómetros, instrumento indudablemente más objetivo (Martínez-Vizcaino y Sánchez-López, 2008;Calahorro et al, 2015). De hecho, existen estudios que comienzan a valorar la AF con acelerometría desde los dos años de edad (Díaz-Quesada et al, 2022). Es cierto que, si se analiza la marca de estos dispositivos inteligentes, el abanico es muy amplio, no existiendo un predominio marcado ni concreto por uno de ellos (Wijndaele et al, 2015).…”
Section: Discussionunclassified
“…Sin embargo, lo que se está observando es que la inactividad física es el cuarto factor de riesgo en lo que respecta a la mortalidad mundial (OMS, 2020). Y esa falta de cumplimentación de recomendaciones saludables comienza a manifestarse en población escolar (Díaz-Quesada et al, 2022).…”
Section: Introductionunclassified
“…To compare groups, a series of inferential statistical tests was performed. The t-test was then computed for independent samples to compare gender (boys vs. girls), In addition, the Student's paired samples t-test was employed to examine the differences between various moments (midweek vs. weekend and school time vs. out-of-school time), in line with previous similar studies [19,30]. A p-value of less than 0.05 was deemed statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Most children spend approximately one-third of the day at school, making school an ideal place to encourage PA from an early age using known daily recommendations to implement PA programs and study PA levels [18,19]. Research examining PA behavior at various times of the day shows that around half of the necessary daily MVPA time should occur during "school time" [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Preschool and daycare settings are considered contexts in which toddler PA can be effectively promoted (Daly-Smith et al, 2020). In these settings, patterns and correlates of PA and sedentary behaviors (SB) have been described by others with some limitations (Díaz-Quesada et al, 2022; Hunter et al, 2019; Kelly et al, 2022; Vega-Perona et al, 2022), and adequate PA levels have been reported among toddlers (aged 2–3 years) during school hours (Díaz-Quesada et al, 2022; Vega-Perona et al, 2022).…”
Section: Introductionmentioning
confidence: 99%